Financial intermediary balance sheet management - Tobias Adrian; Hyun Song Shin (Federal Reserve Bank of New York, 2011)
Conventional discussions of balance sheet management by nonfinancial firms take the set of positive net present value (NPV) projects as given, which in turn determines the size of the firm's assets. The focus is on the composition of equity and debt in funding such assets. In contrast, the balance sheet management of financial intermediaries reveals that it is equity that behaves like the predetermined variable, and the asset size of the bank or financial intermediary is determined by the degree of leverage that is permitted by market conditions. The relative stickiness of equity reveals possible nonpecuniary benefits to bank owners so that they are reluctant to raise new equity, even during boom periods when raising equity is associated with less stigma and, hence, smaller discounts. We explore the empirical evidence for both market-based financial intermediaries such as the Wall Street investment banks, as well as the commercial bank subsidiaries of the large U.S. bank holding companies. We further explore the aggregate consequences of such behavior by the banking sector for the propagation of the financial cycle and securitization.
Keywords: G20; G24; G28; G30; 330; capital; debt; leverage; procyclicality